2021
DOI: 10.1007/s12187-021-09873-6
|View full text |Cite
|
Sign up to set email alerts
|

When the Family Occupies the Future – Self-Processes and Well-Being of Kyrgyz Children and Young People

Abstract: The paper focuses on the question of how young people in the post-Soviet country of Kyrgyzstan deal with the structural and cultural demands of a society characterized by strong obligations of intergenerational solidarity and the normative pattern of submission under the authority of elders. Based on three preponderantly qualitative empirical studies on kindergarten children, teenagers and young adults, young people’s commitment to that order is mapped out, defining their reasons for acceptance on the one hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…heteronormative) family environments have also shown that children rarely question their parents' parenting strategies and generally agree with the expectations and demands set for them (Hunner-Kreisel, Nasrullayeva et al, 2022). Similar findings were published on other Muslim-majority post-Soviet States such as Kyrgyzstan (B ühler-Niederberger & Schwittek, 2022). In part, this is interpreted as a legacy of Soviet educational doctrines, which did not make domestic violence an issue, but warned against 'too much coddling' (Huseynli & Jonson-Reid, 2022).…”
Section: Contextualizing Childhood In Azerbaijansupporting
confidence: 57%
“…heteronormative) family environments have also shown that children rarely question their parents' parenting strategies and generally agree with the expectations and demands set for them (Hunner-Kreisel, Nasrullayeva et al, 2022). Similar findings were published on other Muslim-majority post-Soviet States such as Kyrgyzstan (B ühler-Niederberger & Schwittek, 2022). In part, this is interpreted as a legacy of Soviet educational doctrines, which did not make domestic violence an issue, but warned against 'too much coddling' (Huseynli & Jonson-Reid, 2022).…”
Section: Contextualizing Childhood In Azerbaijansupporting
confidence: 57%